2011
DOI: 10.1088/0963-0252/20/1/015003
|View full text |Cite
|
Sign up to set email alerts
|

Acetylene–argon plasmas measured at a biased substrate electrode for diamond-like carbon deposition: I. Mass spectrometry

Abstract: We report, for the first time, quadrupole mass spectrometry of neutral and positive ionic hydrocarbon species measured at the rf biased substrate electrode of an inductively coupled plasma for acetylene rich C 2 H 2 :Ar mixtures under various bias, frequency and pressure conditions. It has been observed that, irrespective of initial gas mixture, the resultant plasma is dominated by argon neutrals and ions. This is attributed to highly efficient conversion of acetylene to C 2 H due to the enhanced electron dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
49
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 75 publications
8
49
0
Order By: Relevance
“…Thus, C containing sputtered and hydrocarbon species (C, C + , C2H, C2H + , C2H2, C2H2 + ) are likely to be the main constituents of the deposition fluxes. It should be also noted that atomic H is the product specie from several of these reactions listed in Table I, i.e., the discharge employed in the present study is likely to contain large amounts of H including both, neutral and ionized in accordance with previous literature reports [19,30,33]. Moreover, owing to the fact that Ar content in the HiPIMS+DCMS discharges is more than 95%, it should be expected that there is a considerable flux of Ar + ions towards the growing film.…”
Section: A Plasma Chemistrysupporting
confidence: 85%
See 1 more Smart Citation
“…Thus, C containing sputtered and hydrocarbon species (C, C + , C2H, C2H + , C2H2, C2H2 + ) are likely to be the main constituents of the deposition fluxes. It should be also noted that atomic H is the product specie from several of these reactions listed in Table I, i.e., the discharge employed in the present study is likely to contain large amounts of H including both, neutral and ionized in accordance with previous literature reports [19,30,33]. Moreover, owing to the fact that Ar content in the HiPIMS+DCMS discharges is more than 95%, it should be expected that there is a considerable flux of Ar + ions towards the growing film.…”
Section: A Plasma Chemistrysupporting
confidence: 85%
“…Therefore, they take part in the polymerization of parent C2H2 molecules leading to the long-chained poly-acetylene molecules (C2H2)n (n = 1,2,3…) [19] as well as they are lost to the surfaces in the chamber. Doyle et al [30] and Baby et al [33] concluded via experimental investigations and modeled reaction mechanisms that for the diamond-like hydrogenated carbon (DLC:H) growth using C2H2 precursor in RF-PECVD and ICP discharges, the C2H radical is the dominating film forming species. On the other hand, in the plasma based discharges where the ionized fraction of the depositing fluxes reaches close to 100%, C2H2 + and C2H + ions have been identified as the dominating film forming species [27].…”
Section: A Plasma Chemistrymentioning
confidence: 99%
“…Low energy of the impinging atoms provides a low growth rate that can increase the surface mobility of film-forming fragments and, consequently, the density [43]. The low intensity of hydrocarbon radicals detected in these experimental deposition conditions suggests that the main channels of a-CH x growth material take place through carbon sticking to the surface [23] followed by direct atomic hydrogen addition [44]. These mechanisms favour the sp 2 hybridization and generation of a crosslinked polymer-like structure [50], as the present Raman results confirmed.…”
Section: Influence Of the Different Gas Species And Sputtered Particlmentioning
confidence: 88%
“…When the mixture of Ar+H 2 is used, hydrogen species (atom and molecule) are the most influential, specially because atomic hydrogen can create chemisorption sites (dangling bonds) [16,23]. Low energy of the impinging atoms provides a low growth rate that can increase the surface mobility of film-forming fragments and, consequently, the density [43].…”
Section: Influence Of the Different Gas Species And Sputtered Particlmentioning
confidence: 99%
See 1 more Smart Citation